Pengaruh Brand Awareness, Brand Image, dan Brand Trust tehadap Brand Loyalty Pengguna Skincare Skintific: Studi Pada Pelanggan Moisturizer Skintific Melalui E-Commerce Shopee di Wilayah Surabaya - Indah Nurcahyani, Dina; Budi Prabowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study was conducted to determine the influence of brand awareness, brand image and brand trust on brand loyalty of skintific skincare users. This research uses a quantitative type of research with data collection techniques using questionnaire method. The population in this study is skintific moisturizer users who buy via Shopee e-commerce in the Surabaya area. This study used a sample of 100 respondents using a purposive sampling technique with the criteria with a minimum age of 17 years old, domiciled in Surabaya, and have purchased the product at least 2 time of Shopee. The data analysis technique uses multiple linear regression analysis using the validity test, reliability test, classical assumption test, F test, T test, and R2 test using the Statistical Program for Social Science (SPSS) software version 25. The results of the study show that simultaneously Brand awareness, brand image and brand trust have a positive and significant effect on brand loyalty for skintific moisturizer products. Partially, brand awareness has a positive and significant effect on brand loyalty. Brand image does not have a significant effect on brand loyalty. Brand trust has a positive and significant effect on brand loyalty.